Improving crop quality: investigations on soil selenium and zinc transfer and bioavailability - Almutari, Mohammad Mathkar (Kansas State University, 2019)
Management of beneficial and/or essential trace elements, such as Se and Zn, is challenging, and it is complicated by the fact that the margin of safety between the levels that will cause dietary deficiency, and those that result in toxicity, is narrow. This research focused on the ability of the plant system to pretreat wastewaters rich in potentially toxic trace elements and nutrients and enhancing phytoavailability of Zn in Zn-deficient calcareous soils. Plant systems may possess a significant capacity to remediate marginal waters through several phytoremediation processes, including uptake, accumulation, and assisting with biotransformation of inorganic and organic compounds. The aim of the first study was to determine the ability of the halophyte, salicornia europaea, to grow in wastewater or brackish waters and to remove excess trace elements, nutrients, and salts in these highly saline wastewaters. Greenhouse and growth chamber studies were conducted to examine the ability of salicornia europaea to grow and remediate marginal waters. Salicornia europaea showed the ability to remove excess trace elements (Se and B) and salts (Na), indicating salicornia europaea has the potential to be used for precleaning the highly saline wastewaters. Enhanced biomass showed that it can also produce valuable stock for biofuel and bio-based products from marginal waters. Agronomic biofortification is an effective way to increase micronutrient concentrations in grain crops. Formation of dissolved micronutrient-organic C complexations can enhance the solubility of micronutrients. The aims of the second study were to investigate the effectiveness of various Zn sources (organic and inorganic) with and without organic C-based fertilizer co-additives on biofortification of wheat with Zn in a mildly-calcareous soil and to determine distribution (stems/leaves, whole grain, bran and flour) and bioavailability of Zn in different plant parts (bran and flour). A greenhouse experiment was conducted to study wheat grown under different Zn sources. Application of Zn significantly increased grain yield, grain Zn concentration, and Zn bioavailability in white flour. Less soluble ZnO showed more promising results compared to soluble ZnSO4. Co-additives did not improve the soil Zn extractability or the Zn uptake by wheat. Understanding the interactions and speciation of Zn is very important to gain more insights into the fate of added Zn in calcareous soil and also for the efficient management of soil for optimum crop production and environmental conservation. The objectives of the third study were to investigate and understand differences in mobility, extractability, and fractionation of Zn from different sources of granular and liquid Zn, with and without co-additives, in two mildly calcareous soils. A 5-wk long incubation study allowed for spatial evaluation of Zn fate and transport in two soils. Diffusion of Zn was limited to a 0 to 7.5 mm section for all treatments with or without co-additives. The energy dispersive X-ray analysis results were in agreement and revealed that the remaining Zn-incorporated monoammonium phosphate granules, after incubation in soil, contained significant amounts of P and Zn. This study also showed that the liquid Zn sources with no P were better than the co-granulated Zn-P fertilizers.
Keywords: Salicornia europaea; Flue gas desulfurization wastewater; Selenium; Zinc; Agronomic biofortification; Wheat; Co-additives; Zn-fertilizers